2006
DOI: 10.1179/174328006x79481
|View full text |Cite
|
Sign up to set email alerts
|

Process monitoring of fibre reinforced composites using optical fibre sensors

Abstract: The deployment of optical fibre based sensor systems for process monitoring of advanced fibre reinforced organic matrix composites is reviewed. The focus is on thermosetting resins and the various optical and spectroscopy-based techniques that can be used to monitor the processing of these materials. Following brief consideration of the manufacturing methods commonly used in the production of thermoset based composites, a discussion is presented on sensor systems that can be used to facilitate real-time chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 200 publications
(272 reference statements)
0
30
0
Order By: Relevance
“…(3) (4) n A t e 1 1 1 The real (ε') and imaginary (ε") components of the complex permittivity (ε*) are related with the imaginary and real components of the impedance as follows, where, C 0 is the capacitance of the sensor on air. The real part of the permittivity is also named as the dielectric constant of the material, while the imaginary part represents its loss factor.…”
Section: Deamentioning
confidence: 99%
See 1 more Smart Citation
“…(3) (4) n A t e 1 1 1 The real (ε') and imaginary (ε") components of the complex permittivity (ε*) are related with the imaginary and real components of the impedance as follows, where, C 0 is the capacitance of the sensor on air. The real part of the permittivity is also named as the dielectric constant of the material, while the imaginary part represents its loss factor.…”
Section: Deamentioning
confidence: 99%
“…New tendencies in the online cure monitoring of thermoset composites have been studied [3][4][5][6] . Among several cure-monitoring methods, dielectric analysis (DEA) is known to be a well stablished technique for monitoring cure during a production operation 5 and the most mature online cure monitoring technology 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Jensen and colleagues (1992a,b) are among the pioneers to study the influence upon host composite performance following embedment of FOS with regard to orientation and numbers of FOS. Subsequent researchers concluded that the degradation of material strength and modulus is significantly affected by the optical fibre diameter, the FOS orientation relative to nearest plies and the FOS materials (Friebele et al 1999;Zhou et al 2004;Fernando & Degamber 2006). Apart from modifying the diameter and constituent materials of FOS in order to reduce their influence on resulting performance, it is the resin-rich pocket caused by off-axis FOS embedment that draws the attention of most researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, previous studies on the consequences of embedding FOS into FRP composite laminates (e.g. Case & Carman 1994;Friebele et al 1999;Zhou et al 2004;Silva et al 2005;Shivakumar & Bhargava 2005;Fernando & Degamber 2006;Kousourakis et al 2008) are regarded as good comparators. Jensen and colleagues (1992a,b) are among the pioneers to study the influence upon host composite performance following embedment of FOS with regard to orientation and numbers of FOS.…”
Section: Introductionmentioning
confidence: 99%
“…The rate and degree of cure or cross-linking are important parameters as they can have a significant influence on the matrix-dominated properties of fibre-reinforced composites. There is significant on-going interest in the development of techniques to monitor the curing of thermosetting resin systems [1]. The choice of sensors for cure monitoring can be influenced by a number of factors including the following.…”
Section: Introductionmentioning
confidence: 99%